Huge racemose hemangioma of the bronchial artery with arterial supply via the right coronary artery and left internal thoracic artery - Rikako Horie; Kensuke Sekiya; Junichi Funada (Respirology Case Reports, 2022)
Abstract A 79‐year‐old male with bronchiectasis was referred to our clinic because of mild chest tightness on exertion. He had no history of hemoptysis. An electrocardiogram showed ST segment depression in leads V5‐6. Multi‐detector contrast‐enhanced computed tomography revealed no significant stenosis in either coronary artery; however, a huge racemose hemangioma of the bronchial artery (RHBA) was detected. In addition, arterial supply to the RHBA via the right coronary artery (RCA) and the left internal thoracic artery (LITA) was suspected. Adenosine‐loading myocardial scintigraphy images revealed segmental hypo‐perfusion in the left ventricular inferior wall. Selective bronchial artery angiography revealed the huge RHBA. In addition, both the RCA and LITA provided arterial supply to the RHBA. To the best of our knowledge, this case is the first to show multiple arterial supply resulting in a huge RHBA.